Fibroblast growth factor receptor 1 as a putative therapy target in colorectal cancer - Schröck, Friederike; Göke, Antonia; Mäßenhausen, Anne Friederike von; Franzen, Alina; Sharma, Rakesh; Kirsten, Robert; Böhm, Diana; Kristiansen, Glen; Stenzinger, Albrecht; Wynes, Murry; Hirsch, Fred R.; Weichert, Wilko; et al. (Digestion, 2013)
Background/Aims: Resembling a potential therapeutic drug target, fibroblast growth factor receptor 1 (FGFR1) amplification and expression was assessed in 515 human colorectal cancer (CRC) tissue samples, lymph node metastases and CRC cell lines. Methods: FGFR1 amplification status was determined using fluorescence in situ hybridization. Additionally, we assessed protein levels employing Western blots and immunohistochemistry. The FGFR1 mRNA localization was analyzed using mRNA in situ hybridization. Functional studies employed the FGFR inhibitor NVP-BGJ398. Results: Of 454 primary CRCs, 24 displayed FGFR1 amplification. 92/94 lymph node metastases presented the same amplification status as the primary tumor. Of 99 investigated tumors, 18 revealed membranous activated pFGFR1 protein. FGFR1 mRNA levels were independent of the amplification status or pFGFR1 protein occurrence. In vitro, a strong antiproliferative effect of NVP-BGJ398 could be detected in cell lines exhibiting high FGFR1 protein. Conclusion: FGFR1 is a potential therapeutic target in a subset of CRC. FGFR1 protein is likely to represent a central factor limiting the efficacy of FGFR inhibitors. The lack of correlation between its evaluation at genetic/mRNA level and its protein occurrence indicates that the assessment of the receptor at an immunohistochemical level most likely represents a suitable way to assess FGFR1 as a predictive biomarker for patient selection in future clinical trials.